Milk yield, fat yield and fat percentage associations in a Thai multibreed dairy population - Wongpom, Bodin; Koonawootrittriron, Skorn; Elzo, Mauricio A.; Suwanasopee, Thanathip (Agriculture and Natural Resources, 2017)
Milk yield (MY), fat yield (FY) and fat percentage (FP) are important traits for dairy cattle selection and dairy farm profitability in Thailand. Most dairy cattle in Thailand are multibreed, comprising multiple breeds (three from eight breeds per animal). This multibreed composition of dairy animals has generated a large amount of variation in dairy traits among cows raised under farm, tropical environmental conditions across the country. Effective genetic evaluation and selection programs for dairy traits in this population require reliable variance components and genetic parameters estimated under the management, nutritional, health, and climatic conditions in Thai dairy farms. Thus, the objective of this study was to estimate genetic parameters for MY, FY and FP in a Thai dairy multibreed dairy cattle population using farm-collected information. The dataset consisted of pedigree and phenotypic data for MY, FY and FP from 6596 first lactation cows from 687 farms. The data were analyzed using a three-trait (MY, FY and FP), animal mixed model. Fixed effects were herd-year-season, Holstein fraction, heterozygosity and age at first calving. Random effects were animal and residual. An average, information-restricted, maximum likelihood procedure was used to estimate variance components, which in turn were used to compute heritabilities and genetic correlations. Means (SD) were 4315.43 kg (1112 kg) for MY, 157.41 kg (50.42 kg) for FY and 3.59% (0.56%) for FP. Heritability estimates were 0.22 ± 0.06 for MY, 0.17 ± 0.06 for FY and 0.24 ± 0.07 for FP. Genetic correlations were 0.47 ± 0.16 between MY and FY, -0.30 ± 0.20 between MY and FP, and 0.30 ± 0.21 between FY and FP. These estimates of genetic parameters indicated that Thai dairy producers would achieve reasonable amounts of genetic progress if they selected dairy animals based on MY and either FY or FP.